PERANCANGAN DAN UJI KINERJA PISAU PEMARUT KELAPA BERBAHAN STAINLESS STEEL TIPE 201 - Ibrahim, Fajar Nur; Saleh, Agus (Jurnal Mahasiswa Terapan, 2026)
Coconut is one of the resources that has high economic value in various industries. This study aims to design and evaluate the performance of a coconut grater blade made from type 201 stainless steel.The grater blade is a key component in a coconut grating machine, significantly affecting the quality and efficiency of the grating process. In this research, the blade was designed with considerations for mechanical strength, cutting angle, and ease of installation on the machine. Performance testing was conducted to assess the quality of the grated coconut, the time required for the grating process, and the blade’s resistance to wear.The test results showed that the blade made from type 201 stainless steel produced fine and uniform coconut shreds in a relatively short grating time.